2021
DOI: 10.1080/24750263.2020.1857447
|View full text |Cite
|
Sign up to set email alerts
|

Body condition and colonization by fungi of House SparrowsPasser domesticusin the urban and rural environment

Abstract: Mycoses of wild birds are rarely addressed in scientific research. We tested the hypothesis that urban populations of House Sparrow Passer domesticus, which in many cities showed downward trends in their number and are characterized by lower body mass and poorer body condition, would be more frequently colonized by fungi. To evaluate the degree of bird colonization by fungi, swabs were taken from the beak cavity and cloaca of birds from urban and rural populations in the breeding season. A high degree of bird … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…Previous studies found that POC‐measured blood parameters in one or several bird species were also comparable to traditional laboratory assays, even though POC testing devices had slightly higher values compared with the laboratory tests (Beattie et al, 2022; Morales et al, 2020). Our results had similar value ranges (Supporting Information S1: Table 2) compared with many other studies of different passerine species (Beattie et al, 2022; Dulisz et al, 2021; Gadau et al, 2019; Glądalski et al, 2018; Kaliński et al, 2014, 2022; Lieske et al, 2002; McGraw et al, 2020; Morales et al, 2020), which makes POC devices affordable and accessible tools that could be used to study life‐history and blood nutritional physiological parameters in other wild animals. We note that POC devices can measure other hematological variables, such as cholesterol, electrolytes, and hemoglobin concentrations (Livingston et al, 2022; Morales et al, 2020; Sahoo et al, 2022), and we encourage other studies to investigate these additional blood parameters to understand the full efficacy and utility of POC devices with wildlife species.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous studies found that POC‐measured blood parameters in one or several bird species were also comparable to traditional laboratory assays, even though POC testing devices had slightly higher values compared with the laboratory tests (Beattie et al, 2022; Morales et al, 2020). Our results had similar value ranges (Supporting Information S1: Table 2) compared with many other studies of different passerine species (Beattie et al, 2022; Dulisz et al, 2021; Gadau et al, 2019; Glądalski et al, 2018; Kaliński et al, 2014, 2022; Lieske et al, 2002; McGraw et al, 2020; Morales et al, 2020), which makes POC devices affordable and accessible tools that could be used to study life‐history and blood nutritional physiological parameters in other wild animals. We note that POC devices can measure other hematological variables, such as cholesterol, electrolytes, and hemoglobin concentrations (Livingston et al, 2022; Morales et al, 2020; Sahoo et al, 2022), and we encourage other studies to investigate these additional blood parameters to understand the full efficacy and utility of POC devices with wildlife species.…”
Section: Discussionsupporting
confidence: 89%
“…In our analysis examining various biological predictors of levels of each nutritional‐physiological metric, we found that urban house finches in this winter (pre‐breeding) study had higher glucose concentrations than did suburban birds. Previous studies in great tits ( P. major ; Glądalski et al, 2018), blue tits ( Cyanistes caeruleus ; Kaliński et al, 2014), and house sparrows ( P. domesticus ; Dulisz et al, 2021; Gadau et al, 2019) also found a higher concentration of blood glucose in urban birds. These results suggest that food sources in urban locations (e.g., bird feeders) might be more readily available compared with suburban locations, as well as a lower usage of carbohydrates for shorter‐distance flights to forage for energy‐rich resources (Rothe et al, 1987).…”
Section: Discussionmentioning
confidence: 89%
“…N. albida was isolated from a number of wild ducks and teals [ 63 ]. P. laurentii was also isolated from a very limited number of migratory birds, Canadian goose feces, a bird of prey, and a house sparrow [ 64 , 65 , 66 ]. N. globosa was isolated from a bird belonging to the Charadriiforme order [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…When performed in cats and koalas, age was not a determinant of carriage [ 40 , 75 ]. It has been, however, shown that colonization with other fungi (mainly Candida krusei and Candida albicans ) increases with age in house sparrows [ 66 ], suggesting a cumulative risk of carriage with age. Our data seem to be in accordance with the latter result.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation